From attention to action: How streamers, products, and scenes shape customer value co-creation in agricultural livestreaming - Ning, Binyao; Omar, Rosmini; Ye, Ye; Ouyang, Boqiang; Ren, Benhui (Frontiers in Sustainable Food Systems, 2025)
Agricultural livestreaming often struggles to convert viewers from passive spectators into active co-creators of value. Guided by Social Cognitive Theory, this study examines whether and how viewers’ psychological engagement functions as the consumer-side mechanism that links perceived livestream cues to product-centered participation. A structural model was developed integrating streamer characteristics (i.e., credibility, likability, rural identity salience), product attributes (i.e., information, quality, cost-value ratio), and scene features (i.e., authenticity, transparency). Data from a survey of 479 Chinese viewers underwent analysis via PLS-SEM. Findings indicate that all cues except likability exert a substantial effect on psychological engagement, with rural identity salience and scene transparency demonstrating the most pronounced impacts. Psychological engagement substantially predicts four forms of customer participation in value co-creation behaviors: information seeking, information sharing, responsible behavior, and personal interaction, with the first two exhibiting the largest effect sizes. Findings extend Social Cognitive Theory to agri-product commerce by showing that cognitive and affective engagement connects environmental cues to customer participation in value co-creation. Identity-based and scene-based signals carry greater weight than interpersonal warmth in credence-dominant contexts, highlighting a credibility-over-charisma pattern. Practically, the study recommends identity performance by grassroots streamers, scene-transparent storytelling that viewers can verify on camera, clear cost–value communication, and platform features that support multi-angle on-site visuals and real-time interaction.